2018
DOI: 10.15517/ma.v29i3.30105
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de depreciación del peso mexicano sobre el mercado de la carne de cerdo

Abstract: The exchange depreciation serves as a protection mechanism for domestic production and to reduce imports. The objective was to evaluate the effect of two scenarios of exchange rate depreciation on the production, consumption and imports of carcasses pork meat regionally in Mexico in 2015 and 2016. The country was divided into two importation points (internment point one, internment point two) and eight production and consumer regions: Northwest, North, Northeast, Midwest, Central-East, South, East, Yucatan Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The difference between harm to producers and the benefit to consumers, namely $14.0 billion USD, remained in the hands of pork importers and traders, as in Mexico, among other causes, an asymmetric price transmission exists due to an oligopolistic market where retailers tend to quickly pass on price increases to consumers, while delaying the decrease in prices when they have decreased for the producer [ 23 ]. Such is the dependence on the external market that a 15% and 21% currency depreciation of the Mexican Peso would only imply an increase in national production of 0.3% and 0.4%, respectively [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difference between harm to producers and the benefit to consumers, namely $14.0 billion USD, remained in the hands of pork importers and traders, as in Mexico, among other causes, an asymmetric price transmission exists due to an oligopolistic market where retailers tend to quickly pass on price increases to consumers, while delaying the decrease in prices when they have decreased for the producer [ 23 ]. Such is the dependence on the external market that a 15% and 21% currency depreciation of the Mexican Peso would only imply an increase in national production of 0.3% and 0.4%, respectively [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…La utilidad de estos modelos se centra en simular el efecto que tiene en los mercados, la aplicación de medidas de comercio internacional, como cuotas de importación (Rebollar y Posadas, 2023), aranceles ad valorem (impuestos), cuotas compensatorias ad valorem, embargos, economías cerradas, etc. El modelo de equilibrio espacial, se ha utilizado para analizar la competencia interregional y regional en productos agropecuarios, por ejemplo en la industria lechera en Estados Unidos (Chavas, Cox y Jesse, 1993;Yavuz , Zulauf., Schnitkey y Miranda, 1996), en el sorgo mexicano (Rebollar, Hernández y Guzmán, 2016), importaciones de maíz en México (García y Santiago, 2004), en la porcicultura de México (Velázquez, Gómez, Rebollar y Martínez, 2016;Almazán, Rebollar, Velázquez, Gómez y Hernández, 2018), el mercado regional de leche en Japón (Kawaguchi, Suzuki y Kaiser, 1997) y sobre el mercado de la carne de pollo en México .…”
Section: Introductionunclassified
“…Niemi et al ( 24 ) found that the national policy of generally improving the sanitary conditions of pig fattening could reduce the price of pork by up to 5%. Almazan-Figueroa et al ( 25 ) used a non-linear programming model and found that Mexico's rate adjustment would protect domestic producers while harming pork imports and consumers. Song and Cheung ( 26 ) applied the time series analysis method to analyse the impact of pork tariff quotas on household consumption.…”
Section: Introductionmentioning
confidence: 99%